Water oxidation by a soluble iron(iii)–cyclen complex: new findings. Issue 6 (6th January 2016) - Najafpour, Mohammad Mahdi; Safdari, Rasoul; Ebrahimi, Foad; Rafighi, Parvin; Bagheri, Robabeh
Abstract : Herein, the role of iron oxide in the electrochemical water oxidation of an iron cyclen (cyclen = 1, 4, 7, 10-tetraazacyclododecane) is considered. Abstract : Herein, the role of iron oxide in the electrochemical water oxidation of an iron cyclen (cyclen = 1, 4, 7, 10-tetraazacyclododecane) is considered using scanning electron microscopy, energy-dispersive spectrometry, X-ray diffraction, nuclear magnetic resonance spectroscopy, chronoamperometry, cyclic voltammetry and electrochemical impedance spectroscopy.